The Use of Software-Defined Networks to Improve the Performance of Traditional Networks in Serving Important Data - داؤد, ربى; جمال خليفة; مهند عيسى (Latakia University Journal -Engineering Sciences Series, 2023)
Adapting multiple paths between different networks is a valuable and important subject. However, implementing multiple paths within the same internal network can result in the formation of loops and network failure. This problem can be solved by implementing the Spanning Tree Protocol (STP), which is a protocol used to eliminate additional paths between network devices within a single network to prevent loop formation. We can only use multiple paths if each path belongs to different virtual networks. But can we use more than one path within the same local network or within the same virtual network to send data? this is what we have done in this research, where we took advantage of the programmability of software-defined networking (SDN) supporting devices to separate and send loads through different paths based on their importance. The results have shown a good improvement in the delivery of important data.